Status inequality, moral disengagement and violence - Armin Falk (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper studies the causal effect of status differences on moral disengagement and violence. To measure violent behavior, in the experiment, a subject can inflict a painful electric shock on another subject in return for money. We exogenously vary relative status in the realm of sexual attractiveness. In three between-subject conditions, the assigned other subject is either of higher, lower or equal status. The incidence of electric shocks is substantially higher among subjects matched with higher- and lower-status others, relative to subjects matched with equal-status others. This causal evidence on the role of status inequality on violence suggests an important societal cost of economic and social inequalities.
Keywords: A13; C91; D03; Z13; 330; Morality; Violence; Status; Inequality; Laboratory Experiments